2020
DOI: 10.1016/j.ejvs.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Alleviates β-Aminopropionitrile Monofumarate Induced Thoracic Aortic Dissection in C57BL/6 Mice

Abstract: WHAT THIS PAPER ADDS Thoracic aortic dissection (TAD) is a life threatening cardiovascular disorder. Intermittent hypoxia (IH) triggers beneficial effects in multiple physiological systems, such as hypertension and coronary heart disease, in clinical and animal models. It was found that IH alleviates b-aminopropionitrile monofumarate induced TAD in C57BL/6 mice. Future studies should focus on the specific mechanism of thez protective role of IH and whether IH might be a treatment method for TAD. Objective: Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…The consequences of LOX inhibition with BAPN treatment were evidenced by significant elastin fragmentation, aortic wall remodeling, and identification of abnormal cell-matrix interactions, which recapitulate human disease. The mortality rate, aneurysm incidence, and histologic changes associated with BAPN treatment reported by our group are consistent with what others have published using this model (31,33,(43)(44)(45)(46). We demonstrate that moderate aerobic exercise dramatically reduces the incidence of thoracic aortic dissection and aneurysm, pathologic aortic wall remodeling, and associated aortic rupture and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The consequences of LOX inhibition with BAPN treatment were evidenced by significant elastin fragmentation, aortic wall remodeling, and identification of abnormal cell-matrix interactions, which recapitulate human disease. The mortality rate, aneurysm incidence, and histologic changes associated with BAPN treatment reported by our group are consistent with what others have published using this model (31,33,(43)(44)(45)(46). We demonstrate that moderate aerobic exercise dramatically reduces the incidence of thoracic aortic dissection and aneurysm, pathologic aortic wall remodeling, and associated aortic rupture and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The cat K/caspase-8 axis is a key initial step for oxidative stress (47), and cat K ablation is known to mitigate high-fat-diet-induced cardiomyocyte apoptosis and cardiac hypertrophy (48). However, the role of the FGd5-aS1/mir-195/rora axis in cat S/K expression levels was not determined in the present study, although previous studies have demonstrated that cat S and cat K are downregulated in intermittent hypoxia-treated and ischemia-induced mice, respectively (49,50). Moreover, cat K has been revealed to promote proliferation, migration and tube formation of human vascular endothelial cells under hypoxia via acting as target of mir-185-5p and the notch 1 signaling pathway (50,51).…”
Section: Discussionmentioning
confidence: 63%
“…Yet the study of oxygen concentration is still needed to be clari ed, which are primarily due to the different methods of hypoxia (time, oxygen concentration, hypoxia mode, etc.) [7], and the conclusions drawn are not consistent.…”
Section: Introductionmentioning
confidence: 81%
“…It is well established that exercise stimulates the production of epinephrine [8], and hypoxia environment as a stimulus also increases the level of epinephrine [9]. However, the current research methods on hypoxia due to the prolonged exposure to hypoxia, the oxygen concentration is too low, and the pattern of hypoxia is complicated [7], which become limiting factors for the signi cance of clinical application. We expect that our chronic transient hypoxia environment can achieve the effect of exercise, our research found that when mice are exposed to 10% oxygen for one hour every day, it can slow down the weight gain of high-fat-induced obese mice (DIO) and remission the severity of fatty liver, it also activation of AMPK, induction of M2 type macrophage marker CD206 expression in liver and elevated levels of serum epinephrine.…”
Section: Introductionmentioning
confidence: 99%